Effect of irradiation times on the polymerization depth of contemporary fissure sealants with different opacities - Boniek Castillo Dutra Borges; Gabriela Voany Galdino Bezerra; Janaína de Almeida Mesquita; Márcia Rodrigues Pereira; Flávio Henrique Baggio Aguiar; Alex José Souza dos Santos; Isauremi Vieira de Assunção Pinheiro (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The aim of this study was to evaluate the depth of curing of 10 contemporary blue light-activated dental flowable materials at several opacities, influenced by different irradiation times using FT-IR spectroscopy. Fifty-five specimens (n = 5) with a 5-mm diameter and 1-mm thickness of translucent (Opallis Flow T), yellowed (Master Flow A2; Opallis Flow A2; Natural Flow A2; Fluroshield Yellowed), and opaque materials (Master Flow OA2; Natural Flow O; Opallis Flow OA3.5; Opallis Flow OP; Fluroshield White) were obtained at six curing times (10s, 20s, 30s, 40s, 50s, and 60s) using a high-intensity LED (Coltolux, Coltène/Whaledent). The degree of conversion (DC) (%) was obtained using the Nexus 470 FTIR Spectrometer (Nicolet Instruments, USA). The FTIR-ATR spectra for uncured and cured samples were analyzed using a ZnSe crystal. The top and bottom surfaces of the cured specimens were analyzed to obtain the depth of curing. Two-way ANOVA was used to analyze the data. The highest curing depth was obtained by Natural Flow OA2, while the lowest was shown by Master Flow OA2. The shortest curing time generated similar depths of cure in comparison with the most extensive for Opallis Flow A2 and Fluroshield Yellowed. Therefore, depth of curing, influenced by the irradiation time, was dependent on the materials. Using the Natural Flow OA2 opaque sealant and the 10-s curing time for Opallis Flow A2 and Fluroshield Yellowed may represent alternative approaches to sealing tooth fissures.